Orbital Cellulitis Following Uncomplicated Glaucoma Drainage Device Surgery: Case Report and Review of Literature - X. Zheng, Cindy; H. Uhr, Joshua; D. Deaner, Jordan; M. Lin, Michael; J. Moster, Stephen; Razeghinejad, Reza (Journal of Ophthalmic and Vision Research, 2020)
Purpose: Orbital cellulitis (OC) is a rare postoperative complication of glaucoma drainage device (GDD) implantation. To date, there have only been 10 reported cases of OC following GDD implantation. Case Report: Here, we report a case of OC in a 57-year-old man who developed pain, proptosis, and limited extraocular motility two days after uneventful Ahmed FP7 implantation in the right eye. Contrast-enhanced computed tomography of the orbits demonstrated fat stranding and a small fluid collection, consistent with OC. He had minimal improvement with intravenous antibiotics and ultimately underwent GDD explantation. A systematic review of the literature showed that the development of OC following GDD implantation can occur in the early or late postoperative period. Immediate hospitalization with intravenous administration of broad-spectrum antibiotics is recommended. Explantation of the infected GDD is often required for source control. Conclusion: OC is a rare postoperative complication of GDD implantation. Prompt evaluation and treatment are required, often combined with GDD explantation.